School‐ and Family‐Level Socioeconomic Status and Health Behaviors: Multilevel Analysis of a National Survey in Wales, United Kingdom. (April 2015) - Moore, Graham F.; Littlecott, Hannah J.
ABSTRACT BACKGROUND Interventions to address inequalities in adolescent health behaviors often target children from less affluent families, or schools in poorer areas. Few studies have examined whether school‐ or family‐level affluence predicts health behaviors independently, or in combination. METHODS This article reports secondary analysis of the Welsh Health Behavior in School‐aged Children (HBSC) survey. Mixed‐effects logistic regression models test associations of school and family socioeconomic status (SES) with smoking, fruit and vegetable consumption, alcohol consumption, and physical activity. RESULTS Higher family SES was associated with healthier behaviors, except in relation to alcohol consumption. For all behaviors except physical activity, school‐level SES was independently associated with healthier behaviors. In higher SES schools, a stronger association of family SES with health behavior was observed, particularly in relation to smoking and physical activity. CONCLUSIONS School and family SES may exert independent and combined influences upon adolescent health behaviors. Targeting interventions toward deprived schools may fail to address substantial inequalities within more affluent schools. Targeting deprived families may fail to address behaviors of children from affluent families, attending more deprived schools. Identifying universal health improvement interventions which have greater effects among children from poorer backgrounds may be a more effective means of reducing inequalities.